EFEKTIVITAS PEMBERIAN TERAPI TEH DAUN SIRSAK TERHADAP KADAR ASAM URAT PADA PENDERITA GOUT ARTHRITIS DI PUSKESMAS GAMPING II SLEMAN YOGYAKARTA - Istiqomah pancawati p; Sugeng Sugeng; Agus Sarwo Prayogi (Jurnal Kesehatan Karya Husada, 2014)
Background : Gout (uric acid)is a crystalline acid into uric acid substances purin. The prevalence of gout arthritis in the U.S. population is estimated at 13.6 / 100,000 population, while in Indonesia alone an estimated 1.6 to 13.6 / 100,000 people, the prevalence increases with age. In indonesia ranks second all ethnic attack. Of the preliminary study will be undertaken during the last 3 months is december 152 people, january 165 people, february147 people affected by gout. Purpose: To determine the effectiveness of the provision of soursop leaf tea in lowering uric acid levels gout sufferers Methods : This research is a quasi experimental study with a pretest-posttest design with nonrandomized control design with a sample of 48 respondents, were divided into 2 groups the experimental group and 24 respondents, 24 respondents control group. Sampling is used way is by measuring the levels of uric acid in advance before being given the tea leaves of the soursop (pretest) and then the tea is given to the respondent to drink for 7 days in the morning and evening after it was measured again to determine the uric acid levels decline. The analysis used is Test Paired T Test and T Test. Results: From research that has been done in getting the results that in the control group and the experimental group, largely male dominated (62.5%) in the control group and 14 (41.7%) in the experimental group. Agein the control groupwas dominated by age between 51-60 years (45.8%), where as the experimental group age between 61-70 years (33.3%). Type of workin the control group, largely dominated by self-employed as many as8 people(33.3%), while the experimental group was dominated by house wives and self-employedas many as 8 people (33.3%). Conclusion: Based on research results obtained, it can be concluded that gout sufferers are dominated by males between the age of 51-60 years in the Clinic Gamping II SlemanYogyakarta in 2013.